Development of Teaching Materials for Facilitation and Management of Changes in Community Empowerment - Sasmita, Karta; Kuswantono, Sri; Hadiyanti, Puji; Ikhsanudin, Ikhsanudin (Journal of Nonformal Education, 2021)
The facilitation and management of changes can support the success of community empowerment. In the process, appropriate facilitation and management of changes in teaching materials are needed. This study aims to construct the teaching materials for facilitation strategies and management of changes by Indonesian society's socio-cultural characteristics. The research and development method was carried out using the Borg and Gall model to achieve this goal. The result shows that the teaching material needed in the facilitation strategy and management of changes includes three aspects: knowledge, skills, and attitudes. Overall, facilitators know empowerment facilitation but still feel they lack facilitation skills in practices. The personal communication skills most needed are probing and paraphrasing. The collaboration skills most wanted to improve in the community group are building group dynamics and teamwork, building belief and confidence, encouraging full participation, supporting conflict resolution, encouraging inclusive solutions, giving and receiving feedback, encouraging mutual understanding, and monitoring the role and group level. The most preferred attitudes for a community empowerment facilitator are unconditional trust in group abilities, building empathy, building interest in others, and an unconditional positive outlook. According to the audience, suitable teaching materials use easy-to-understand language, illustrated pictures or videos that work well, and include real examples in the field. Teaching materials must be designed to be attractive and user-friendly. In this case, it can be done in further research.